Frequency of Inferior Vena Caval Abnormalcy due to a Juxtaposed Pathology - Costa, D.; Ramanathan, H. P.; Merchant, S. (Nuklearmedizin - NuclearMedicine, 1977)
Radionuclide inferior vena cavagrams were done in 135 patients who had hepatomegaly, splenomegaly or a mass in the vicinity of the inferior vena cava (I. V. C.). 2-5mCi 99mTc phytate, 99mTc S colloid, 99mTc O4-, 99mTc-LIDA, 99mTc pyridoxyledene glutamate or 113min colloid were injected directly and rapidly into either a malleolar or a femoral vein while the patient lay supine under the 13.5 detector head of a scinticamera. Rapid sequential scintiphotos were manually taken at approximately 1 sec. interval for 20-30 sec. Thus iliac vein, I. V. C., cardiopulmonary zone in infants, aorta and the arterial phase were visualized.48 % of these subjets had an abnormal I . V . C . and the depictions were interestingly varied, indicating that different patients responded in a different manner even to grossly similar pathologies. It became evident that this soft walled vessel could be compressed by both fluids and neoplastic tissue (Fig. 1,2); the long I. V. C. channel could also be segmentally pushed away by a mass in its vicinity. (Fig. 2, 3, 4). An abnormal arterial flush usually differentiated between benign (Fig. 2) and malignant (Fig. 3) lesions, even when the mass was extra-hepatic (Fig. 4) and retroperitoneal (Fig. 5).Such a systematic study of I. V. C. had not been possible earlier since the classical x-ray contrast inferior vena cavagram necessitates venous dissection, passage of a catheter, and the injection of large volume of fluid under an unphysiologically high pressure. The simplified radionuclide technique, however, permitted the study of neonates and critically ill subjects with massive ascites, while retaining a satisfactory reproducability (Fig. 6).